2006
DOI: 10.3164/jcbn.39.3
|View full text |Cite
|
Sign up to set email alerts
|

What has been Learned from the Studies of Oxidative Stress-induced Carcinogenesis: Proposal of the Concept of Oxygenomics

Abstract: Summary Epidemiological studies have demonstrated that oxidative stress associated with a variety of pathological conditions is one of the major causes of carcinogenesis. Reactive oxygen and nitrogen species contribute to genomic alterations, presumably followed by selection of the best-adapted proliferating cells in a given environment. Recent data suggest that there exist common signaling pathways for oxidative stress-associated carcinogenesis. So far, oxidative DNA damage has been assumed to be randomly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…29,30 In the edge region of the helium APP jet, it was reported that the ambient air was mixed in the plasma and the amount of the ROS was increased. 29,30 In the edge region of the helium APP jet, it was reported that the ambient air was mixed in the plasma and the amount of the ROS was increased.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…29,30 In the edge region of the helium APP jet, it was reported that the ambient air was mixed in the plasma and the amount of the ROS was increased. 29,30 In the edge region of the helium APP jet, it was reported that the ambient air was mixed in the plasma and the amount of the ROS was increased.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…Our current conclusion is that there are target genes, such as p15 / p16 , in oxidative stressā€induced carcinogenesis as described above . Then, the next question would be whether there are any fragile sites in the genome against oxidative stress . There are many types of DNA damage, including single and double strand breaks, base modifications, abasic sites and crossā€links .…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, iron reduction could make lower risk of hepatic likely other cancers . Akatsuka et al . demonstrate that oxidative stress caused extensive genomic alterations in the cancer genome at the chromosomal level in Feā€NTAā€induced rat renal cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%